Multiple Diversity of Mitochondrial Cytochrome b Amino Acid Sequences of the Same Length in Animals - Zamyatnin, Alexander A.; Belozerskaya, Tatiana A. (Frontiers in Molecular Biosciences, 2020)
The size of natural peptide molecules can be considered as the number of amino acid residues p. The aim of the work was to analyse the region of existence and occurrence of natural peptide structures formed as a result of matrix synthesis on the p-scale. The object of the study was the Swiss-Prot database consisting of more than 5.6•105 primary peptide structures which were fully determined (complete sequence). Structures containing non-standard amino acid residues, as well as identical copies of amino acid sequences, were removed from them. The remaining 463,450 different amino acid sequences with a length of 2 to 35,213 residues were used for further analysis. It was shown that the peptide structures of different biological domains and kingdoms are characterized by different regions of existence, and the profile shapes of the obtained curves are close to a number of known distributions. At the same time, they have sharp high peaks, indicating the existence of a large number of specific molecules with the same p-value. One of these peaks characterizes more than 1,000 different amino acid sequences of mitochondrial cytochrome b molecules at p=359. Such examples may indicate that the most perfect polypeptide structures were selected in the evolutionary process to perform this function. As a result, many protein molecules with different amino acid sequences of the same length and characterized by the same functions were formed.